2011
DOI: 10.1002/aenm.201100001
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Carbon Nanotubes Grown on Graphene Paper as Electrodes in Lithium‐Ion Batteries and Dye‐Sensitized Solar Cells

Abstract: Vertically aligned carbon nanotubes (VACNTs) possess the advantages of a high degree of order, good controllability, and easy manipulation. Thus, their synthesis, properties, and potential for applications have been intensively investigated. [1][2][3][4][5] VACNTs are usually grown by chemical vapor deposition (CVD) on substrates with pre-deposited catalysts. Due to the rigorous CVD synthesis conditions, substrates employed for VACNT growth should be thermally and chemically stable materials, such as SiO 2 /Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
181
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(186 citation statements)
references
References 30 publications
1
181
1
1
Order By: Relevance
“…[ 60 ] Despite previous papers claimed a certain fragility of bare RGO paper electrodes, [ 35 ] these last two research efforts clearly demonstrated that the introduction of defects, or the direct functionalization of RGO's surface with other electroactive species, could enable fl exible graphene-based electrodes. Similarly, other research efforts on N-doped RGO [ 61 ] and RGO paper functionalized with CNT [ 62,63 ] were reported, but no substantial improvement in terms of electrochemical performance could be observed (Table 1 ). Moreover, a chemically activated RGO paper was also tested as LIB anode [ 64 ] but, unfortunately, it showed very poor performance (i.e., 1 st cycle irreversible capacity of about 86% and a lithiation capacity retention of about 16% after 10 cycles at 20 mA g −1 ) ( Table 1 ).…”
Section: Continuedmentioning
confidence: 60%
“…[ 60 ] Despite previous papers claimed a certain fragility of bare RGO paper electrodes, [ 35 ] these last two research efforts clearly demonstrated that the introduction of defects, or the direct functionalization of RGO's surface with other electroactive species, could enable fl exible graphene-based electrodes. Similarly, other research efforts on N-doped RGO [ 61 ] and RGO paper functionalized with CNT [ 62,63 ] were reported, but no substantial improvement in terms of electrochemical performance could be observed (Table 1 ). Moreover, a chemically activated RGO paper was also tested as LIB anode [ 64 ] but, unfortunately, it showed very poor performance (i.e., 1 st cycle irreversible capacity of about 86% and a lithiation capacity retention of about 16% after 10 cycles at 20 mA g −1 ) ( Table 1 ).…”
Section: Continuedmentioning
confidence: 60%
“…13), graphene (approximately 568 mA h g À 1 ) (ref. 14) and carbon nanotube and graphene composites 15,16 . In addition, partially graphitized porous carbon is a class of emerging materials with promising chemical properties for LIBs due to their relatively low cost, high conductivity and porous structure, which make them very attractive materials.…”
mentioning
confidence: 99%
“…[197], Copyright 2017, Nature Group aligned SWCNT array also displayed a high conversion efficiency of 5.5%, comparable to 5.6% obtained with a Pt-based DSSC tested under the same conditions [195]. In addition, carbon catalysts comprised of CNTs coated onto a flexible graphene paper achieved 83% conversion efficiency of that of a Pt electrode [196].…”
Section: Carbon-based Metal-free Catalysts For Solar Cells and Metal-mentioning
confidence: 53%